Colour Changes of Tooth-Coloured Materials in the Different Solutions - Yanikoglu, Nuran; Yesil Duymus, Zeynep; Meral, Kadem (Asian Journal of Chemistry, 2010)
The purpose of this study is to evaluate the effect of material (light polymerized composite versus heat-polymerized acrylic), surface smoothness (rough versus smooth), staining solution (coffee, tea, Turkish coffee, distilled water or mouthwash) and time (baseline, 7 and 30 days) on colour change in a sample of tooth-coloured resins. Twenty-four specimens of each material were evaluated before and after 1, 7 and 30 days of exposure to the different solutions (coffee, tea, Turkish coffee and distilled water) at a constant temperature of 37 ± 1 °C. In addition, 6 specimens were evaluated before and after 6, 12 and 24 h immersion in mouthwash (Andorex; Kim Pa, Istanbul, Turkey). Colour changes (DA) of materials were analyzed by use of a spectrophotometer. Data were analyzed with three-way analysis of variance (ANOVA). The highest mean value (DA) for the Turkish coffee was 0.98. The light-polymerized composite material tested was the least colour stable.